Ethanol Extract of Choerospondias axillaris Fruit Pulp Enhances Haematological Parameters in Oncorhynchus mykiss Cultured in Nepal - Shakya, Shubha Ratna; Labh, Shyam Narayan (Nepal Journal of Biotechnology, 2019)
The present outdoor experiment was carried out to evaluate the effect of dietary supplementation of lapsi Choerospondias axillaris (Roxburgh, 1832) on haematological parameters in rainbow trout Oncorhynchus mykiss in Nepal. The lapsi fruits were obtained from local market of Kathmandu. The feeding trail was conducted for 90 days. About 270 trout with similar body weight (5±1g) were distributed randomly at the rate of 15 fishes per cage (1m3) into 18 cages placed in raceway pond. Six practical diets containing 40% protein were prepared as T1 (0.0 g kg-1) T2 (0.1 g kg-1), T3 (0.2 g kg-1), T4 (0.4 g kg-1), T5 (0.8 g kg-1) and T6 (1.6 g kg-1) supplemented by the ethanol extract of lapsi fruits along with other usual ingredients viz. fish meal, wheat flour and cod liver oil etc. At the end of the experiment the haematological parameters were measured. A significant difference (P< 0.05) in haematological parameters was observed between the treated diets fed groups to that of control diet fed group. Total erythrocytes count (RBC), Haematocrit (Hct), Haemoglobin concentration (Hb), and erythrocyte indexes (MCV, MCH and MCHC) were found significantly higher in T4 (0.4 %) diet fed trout as compared to the control. A minimum of 0.4 % (0.4g kg-1) lapsi fruit extract in fish feeds gave more increase in haematological parameters of Oncorhynchus mykiss. Inclusion of lapsi fruit extract at 0.4 % concentration is therefore could be used effectively in aquaculture.